Trends in Population Growth and Forest Cover Change in Tanzania (From 1980 Until 2018) - Kahyarara, Godius (Tanzania Journal for Population studies and Development, 2008)
This paper examines the effect of population growth on the size of Tanzania’s forest cover by assessing the extent to which the growing demand for forest goods and services from rapid expanding population lead to deforestation. Using long span of data, the paper predicts future demand of forest products, size of forest cover, and population in the next ten years (up to 2018). The statistical analysis of forecasting models estimated in the paper confirms that unprecedented growth in population of Tanzania accounts for the loss of forest cover in Tanzania. Considering the annual population growth rate of about 3%, the paper demonstrates that the population will reach 53.4 millions in the next ten years. Furthermore, the forecasting model estimates that forest cover will decline by 11%. The paper further shows that within a time span of ten years from 1990 to 2000 the forest cover changed by 10.8%. The aggregate forecasting results on forest cover change show that in a time span of 25 years, forest cover in the country will have declined by nearly a quarter. The paper concludes that a positive correlation between growth in population and use of forest products calls for an integration of population policies and programs with forest management strategies. Use of alternative resources such as LPG and natural gases to reduce pressure on wood fuel, tree planting, and sustainable forest management plans can potentially help to reduce pressure on the forest cover, thereby curbing deforestation in Tanzania that is fuelled by expanding needs of a growing population.